South Korea in the ASEAN-centered regional network - Teo, Sarah (2023)
Relying on a networked perspective, this article argues that South Korea is an actor of relative importance in ASEAN's regional network, but it ultimately does not occupy a place that is more crucial than the association's other dialogue partners. In the context of ASEAN seeking to maintain its network power in an evolving Indo-Pacific, South Korea has played a supportive role in ASEAN's pursuit of social access, brokerage links and minimizing its exit potential from the Indo-Pacific network. South Korea's role, however, has been a comparably limited one rooted in specific functional areas and focused on certain ASEAN member states. While these efforts would certainly reinforce ASEAN's network power to some extent, the relatively thin network links between ASEAN and South Korea in other sectors suggest that there is little potential to expand cooperation beyond a functional and socioeconomic trajectory.